Wound electrode body and battery
By setting the appropriate distance between the termination glue and the positive electrode layer in the wound electrode body of the lithium-ion battery and doping metal elements into the ternary material, the problems of degradation in performance and local lithium-ion battery during recycling are solved, and the performance and stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202411822764.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
AI Technical Summary
There are problems with degradation in battery performance and local lithium-ion evolution during recycling of existing lithium-ion batteries. This is mainly due to the side reaction between Ni (nickel) in the positive electrode active substance of the ternary material and the electrolyte, resulting in the swelling of the glue edge, and the diffusion of lithium ions leads to the reduction of local CB value.
By providing the first and second empty foil areas in the positive electrode sheet of the wound electrode body, and applying the first and second termination glues on these areas, it is ensured that the termination glue is maintained at an appropriate distance from the positive electrode active material layer to avoid diffusion of lithium ions. At the same time, metal elements are doped in the ternary material of the positive electrode active material layer to improve the structural stability of the material.
Effectively alleviate or avoid the local lithium-ion problem caused by higher lithium ion concentration at the edge of the stop glue than the rest of the area, improve the overall performance of the battery, and extend the time of cycle capacity attenuation and side reactions.
Smart Images

Figure CN119627249A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular, to a wound electrode body and a battery. Background Art
[0002] Batteries have the advantages of high energy density, long life and environmental friendliness, making them the preferred power source in fields such as mobile electronic devices and electric vehicles.
[0003] The battery cell consists of a positive electrode, a negative electrode, an electrolyte and a separator. During the charge and discharge process, lithium ions are intercalated and deintercalated back and forth between the two electrodes. During charging, lithium ions are deintercalated from the positive electrode and intercalated into the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; during discharge, the opposite is true. As one of the core components of the battery, the structure and performance of the positive electrode directly affect the overall performance of the battery.
[0004] Currently, the battery has problems of battery performance degradation and local lithium plating. Summary of the invention
[0005] In view of this, an embodiment of the present application provides a wound electrode body and a battery having the same, so as to improve the problems of battery performance degradation and local lithium deposition.
[0006] In the first aspect, the embodiment of the present application provides a wound electrode body. The wound electrode body includes a positive electrode sheet, a negative electrode sheet and a separator arranged in a stacked manner. The positive electrode sheet and the negative electrode sheet are wound with the separator interposed therebetween, and the wound electrode body has a flat portion and a curved portion. The positive electrode sheet includes a positive electrode collector and a positive electrode active material layer. Along the first direction Z, the positive electrode collector has a first surface and a second surface arranged opposite to each other. The first surface is provided with a first paste coating area and a first empty foil area located at the tail of the positive electrode collector, and the second surface is provided with a second paste coating area and a second empty foil area located at the tail of the positive electrode collector. The positive electrode active material layer includes a first positive electrode active material layer arranged on the first paste coating area and a second positive electrode active material layer arranged in the second paste coating area, and the positive electrode active material layer includes a positive electrode active material. Along the second direction X perpendicular to the first direction Z, at least part of the first empty foil area is provided with a first termination glue, and the spacing between the side of the first termination glue close to the first positive electrode active material layer and the edge of the first positive electrode active material layer close to the first termination glue is d1, and d1≥0. The positive electrode active material is Li[Ni x Co y Mn z M 1-x-y-z ]O2 ternary material, M is the metal element doped in the ternary material, 1-xyz>0.
[0007] Additionally or alternatively, along the second direction X, at least part of the second empty foil area is provided with a second stop glue, and the distance between the side of the second stop glue close to the second positive electrode active material layer and the edge of the second positive electrode active material layer close to the second stop glue is d2, d2≥0.
[0008] Additionally or alternatively, d1 satisfies 0<d1≤A / (B1*2); and / or, d2 satisfies 0<d2≤A / (B2*2). Preferably, A is 30μm to 100μm, and B1 and B2 are 15μm to 30μm, respectively. More preferably, A is 50μm to 80μm, and B1 and B2 are 20μm to 25μm, respectively. A is the single-sided paste thickness of the positive electrode sheet, B1 is the thickness of the first termination glue, B2 is the thickness of the second termination glue, and the units of d1 and d2 are mm.
[0009] In addition or alternatively, the end of the first positive electrode active layer near the first paste coating area of the first termination glue is provided with a rounded corner or a chamfer; and / or, the end of the second positive electrode active layer near the second paste coating area of the second termination glue is provided with a rounded corner or a chamfer. Preferably, when the end of the first positive electrode active material layer and / or the end of the second positive electrode active material layer is provided with a rounded corner, the radius of the rounded corner is 1mm to 10mm; more preferably, the radius of the rounded corner is 2mm to 6mm.
[0010] Additionally or alternatively, in the ternary material, 0.5≤x<1, 0≤y≤0.2, 0≤z≤0.3, preferably, 0.8≤x<1, 0≤y≤0.1, 0≤z≤0.1; and / or M includes at least one of B, Al, Zr, W, Ta, Nb, Ti, Fe, Y, Ga, Cu, Zn, Ge, Mo, V and Cr.
[0011] In addition or alternatively, the mass percentage of single crystal in the positive electrode active material is 50% to 100%, and the mass percentage of polycrystalline is 0% to 50%. Preferably, the mass percentage of single crystal in the positive electrode active material is 80wt% to 98wt%, and the mass percentage of polycrystalline is 2wt% to 20wt%.
[0012] Additionally or alternatively, the specific surface area of the ternary material is 0.5 m 2 / g~1.5m 2 / g, preferably, the specific surface area of the ternary material is 0.8m 2 / g~1.2m 2 / g; and / or
[0013] D of ternary materials 50 2μm~12μm, D max It is 15μm~25μm.
[0014] Additionally or alternatively, the first surface faces the winding center of the wound electrode body, the second surface is away from the winding center, and the compaction density of the positive electrode active material layer is 3.0 g / cm 3 ~3.5g / cm 3 ; and / or the surface density of the positive electrode active material layer is 12 mg / cm 2 ~25mg / cm 2 ; and / or the surface resistance of the positive electrode sheet is 150mΩ~300mΩ.
[0015] Additionally or alternatively, the first surface faces the winding center of the wound electrode body, and the second surface is away from the winding center. At least in the bending portion, the surface density of the first positive active material layer of the positive electrode sheet is less than the surface density of the second positive active material layer of the positive electrode sheet. Preferably, at least in the bending portion, the surface density of the first positive active material layer is 90% to 99% of the surface density of the second positive active material layer. More preferably, at least in the bending portion, the surface density of the first positive active material layer is 94% to 97% of the surface density of the second positive active material layer; and / or, at least in the bending portion, the thickness of the first positive active material layer is h1, the thickness of the second positive active material layer is h2, h1<h2; and / or, at least in the bending portion, the first positive active material layer is provided with holes or a concave texture structure.
[0016] Additionally or alternatively, the surface density of the first positive electrode active material layer is smaller than that of the second positive electrode active material layer. Preferably, the surface density of the first positive electrode active material layer is 90% to 99% of that of the second positive electrode active material layer. More preferably, the surface density of the first positive electrode active material layer is 94% to 97% of that of the second positive electrode active material layer. And / or, the thickness of the first positive electrode active material layer is h1, the thickness of the second positive electrode active material layer is h2, h1<h2. And / or, the first positive electrode active material layer is provided with holes or a concave texture structure.
[0017] In addition or alternatively, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer. Along the first direction Z, the negative electrode current collector has a third surface and a fourth surface arranged opposite to each other, the third surface faces the winding center, and the fourth surface faces away from the winding center. The negative electrode active material layer includes a first negative electrode active material layer and a second negative electrode active material layer respectively arranged on the third surface and the fourth surface. At least in the bending portion, the N / P ratio of the second negative electrode active material layer to the first positive electrode active material layer is greater than the N / P ratio of the first negative electrode active material layer to the second positive electrode active material layer, and the difference between the two is 0.005 to 0.2. Preferably, the difference between the two is 0.02 to 0.08. The N / P ratio is the negative electrode capacity per unit area / positive electrode capacity per unit area.
[0018] Additionally or alternatively, the N / P ratio of the second negative electrode active material layer to the first positive electrode active material layer is greater than the N / P ratio of the first negative electrode active material layer to the second positive electrode active material layer, and the difference between the two is 0.005 to 0.2. Preferably, the difference between the two is 0.02 to 0.08.
[0019] In a second aspect, an embodiment of the present application provides a battery, which includes a wound electrode body according to any of the above embodiments.
[0020] During the recycling process of lithium-ion batteries, a series of side reactions such as the high-valence Ni (nickel) in the positive electrode active material of the ternary material and the generation of gas in the electrolyte make the edge of the termination gel prone to swelling. At this time, some lithium ions (Li+) in the positive electrode active material layer in the area covered by the termination gel will diffuse to the edge of the termination gel. This will cause the Li+ concentration at the edge of the termination gel to be higher than that in the rest of the area, making the local CB value smaller, resulting in lithium precipitation problems, which in turn affects the performance of the battery. According to the positive electrode sheet provided in the embodiment of the present application, on the first aspect, by making the side edge of the first termination glue attached to the first empty foil area just contact or maintain a certain distance with the edge of the first positive electrode active material layer on the paste area close to the first termination glue, it is improved and avoided that during the recycling process of the lithium-ion battery, the high-valence Ni (nickel) and the electrolyte in the ternary material positive electrode active material produce a series of side reactions, which makes the edge position of the first termination glue easy to swell, resulting in some lithium ions (Li+) in the first positive electrode active material layer in the termination glue covered area diffusing to the edge of the first termination glue. Furthermore, the lithium ion concentration at the edge of the first termination gel is higher than that in the rest of the first positive electrode active material layer, resulting in a smaller local CB value and local lithium precipitation, which can reduce or avoid the problem, and further improve the performance of the battery; secondly, by doping metal elements into the ternary material positive active material in the positive electrode active material layer, the structural stability of the ternary material can be improved, and the battery cycle capacity attenuation caused by the decrease in material structural stability caused by the H2-H3 phase change of lithium in the insertion / deinsertion process during charging and discharging and the side reactions with the electrolyte can be reduced, the side reactions between the ternary positive electrode material and the electrolyte can be slowed down, and the problems of lithium precipitation at the edge of the termination gel and the decline in battery performance can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a schematic diagram of the structure of the positive electrode termination glue in the related art.
[0022] Figure 2 It is a schematic diagram of the three-dimensional structure of a wound electrode body provided according to one embodiment of the present application.
[0023] Figure 3 for Figure 2Cross-sectional view along DD of the wound electrode body.
[0024] Figure 4 A schematic diagram of a positive electrode sheet structure provided according to an embodiment of the present application.
[0025] Figure 5 This is a schematic diagram of the structure of a positive electrode sheet provided according to another embodiment of the present application.
[0026] Figure 6 A schematic diagram of a negative electrode sheet structure provided according to an embodiment of the present application.
[0027] Figure 7 Schematic diagram of a battery according to one embodiment of the present application.
[0028] Figure 8 FIG. 1 is a schematic diagram of a battery according to another embodiment of the present application.
[0029] Reference numerals:
[0030] 1000. Battery;
[0031] 100, wound electrode body; 101, bent portion; 101a, first bent portion; 101b, second bent portion; 102, flat portion;
[0032] 10 / 10', positive electrode sheet; 11, positive electrode active material layer; 11a, first positive electrode active material layer; 11b / 11b', second positive electrode active material layer; 12 / 12', positive electrode current collector; 13, pole ear; 14, first paste coating area; 15 / 15', second paste coating area; 16, first empty foil area; 17 / 17', second empty foil area; 18, termination glue; 18a, first termination glue; 18b / 18b', second termination glue; 19a, first surface; 19b / 19b', second surface;
[0033] 20, negative electrode sheet; 21, negative electrode active material layer; 21a, first negative electrode active material layer; 21b, second negative electrode active material layer; 22, negative electrode current collector; 23, third surface, 24, fourth surface;
[0034] 200, housing;
[0035] 30. Diaphragm. DETAILED DESCRIPTION
[0036] Generally, the electrode body of a lithium-ion battery can be formed by stacking a positive electrode sheet, a negative electrode sheet and a separator. Taking a wound electrode body as an example, it can include a stacked positive electrode sheet, a negative electrode sheet and a separator. The positive electrode sheet and the negative electrode sheet are wound with the separator between them to form a wound electrode body with a flat portion and a curved portion.
[0037] As one of the key components of the electrode body, the structure and performance of the positive electrode sheet directly affect the overall performance of the lithium-ion battery. Taking the wound electrode body as an example, along the first direction, i.e., the thickness direction of the electrode sheet, the positive electrode current collector of the positive electrode sheet has two surfaces arranged opposite to each other. Along the second direction, i.e., the length direction of the electrode sheet, both surfaces are provided with an empty foil area and a paste area. For example, Figure 1 In the example, the second surface 19b' is provided with a second pasted area 15' and a second empty foil area 17' located at the tail of the positive current collector 12'. A positive active material layer is provided on the pasted area, for example, a positive active material layer 11b' is provided on the second pasted area 15'.
[0038] It should be noted that the first direction in the text is the Z direction described in the figure, that is, the thickness direction of the pole piece, and the second direction is the X direction shown in the figure, that is, the length direction of the pole piece. At the same time, the direction perpendicular to the first direction Z and the second direction X is the Y direction shown in the figure, that is, the width direction of the pole piece.
[0039] The positive active materials in the positive active material layer of traditional lithium-ion batteries are generally lithium cobalt oxide and lithium iron phosphate, which have good cycle stability and safety. However, the gram capacity of these positive active materials is low, which is difficult to meet the demand for high energy density lithium-ion batteries in electrical equipment such as new energy vehicles.
[0040] In the related technology, in order to increase the gram capacity of the positive electrode active material, so as to improve the energy density of lithium-ion batteries and further increase the market share of lithium-ion batteries in power lithium-ion batteries for new energy vehicles, layered nickel-cobalt-manganese (NCM) ternary materials with higher gram capacity are used as positive electrode active materials. However, the existing nickel-cobalt-manganese ternary materials have the problem of poor material structure stability during the lithium-ion cycle, which leads to a rapid decline in the performance of lithium-ion batteries.
[0041] For example, in the charging state, high-valence Ni (nickel) and electrolyte will produce a series of side reactions, resulting in a decrease in battery performance. In addition, in practical applications, most ternary positive electrode materials are secondary spherical polycrystalline materials formed by the agglomeration of nanoscale primary particles or single polycrystalline blends. There are a large number of grain boundaries inside the polycrystalline NCM. The inventors have found that during the battery charging and discharging process, due to the anisotropic lattice changes, polycrystalline NCM is prone to grain boundary cracking, which can easily lead to the breakage of secondary particles, thereby causing the specific surface area and interface side reactions of the polycrystalline NCM to increase rapidly, resulting in an increase in battery impedance and a rapid decrease in performance.
[0042] As mentioned above, in order to prevent the empty foil area from directly contacting the negative electrode sheet and causing a short circuit, a stop glue is placed on the empty foil area in the wound electrode body. Figure 1As shown in the example, in the positive electrode sheet 10', a second stop glue 18b' is provided on the second empty foil area 17' of the second surface 19b' of the positive current collector 12', and the second stop glue 18b' will partially cover the second positive electrode active material layer 11b' provided on the second paste area 15' at the starting end. Similarly, a first stop glue is provided on the first empty foil area of the first surface of the positive current collector 12', and the first stop glue will partially cover the first positive electrode active material layer provided on the first paste area at the starting end (not shown in the figure).
[0043] The inventors have found that during the cyclic use of lithium-ion batteries, the high-valence Ni (nickel) in the above-mentioned ternary material positive electrode active material and the electrolyte produce a series of side reactions, which makes the edge of the termination glue 18 prone to swelling. Figure 1 As shown in the example, some lithium ions (Li+) in the second positive electrode active material layer 11b' in the area covered by the second termination glue 18b' will diffuse to the edge of the second termination glue 18b'. This will cause the Li+ concentration at the edge of the second termination glue 18b' to be higher than that in the rest of the area, making the local CB value smaller, thereby causing lithium precipitation problems, further affecting the performance of the battery (for example, causing the performance of the lithium-ion battery to deteriorate).
[0044] In order to improve the above situation, the present application provides a wound electrode body and a battery. Figures 2 to 8 , the embodiments of the present application are described.
[0045] It should be understood that there may be many ways to implement the present application, and it should not be construed as being limited to the embodiments described herein. The embodiments described herein are only for a more thorough and clear understanding of the present application.
[0046] Exemplary wound electrode body
[0047] See 2 and Figure 3 , the present application embodiment provides a wound electrode body 100. The wound electrode body may include a positive electrode sheet 10, a negative electrode sheet 20 and a separator 30 arranged in a stacked manner. Figure 2 and Figure 3 As shown, the positive electrode sheet 10 and the negative electrode sheet 20 are wound with the separator 30 to form a wound electrode body 100 having a flat portion 102 and two curved portions 101. The two curved portions 101 (i.e., the first curved portion 101a and the second curved portion 101b) are distributed at opposite ends of the flat portion 102 along the width direction. The first curved portion 101a and the second curved portion 101b are collectively referred to as curved portions 101.
[0048] By way of example only, the negative electrode sheet 20 may include a negative electrode current collector 22 and a negative electrode active material layer 21 disposed on the negative electrode current collector. Figure 6Along the first direction Z, the negative electrode current collector 22 has a third surface 23 and a fourth surface 24 arranged opposite to each other, the third surface 23 faces the winding center, and the fourth surface 24 faces away from the winding center, and the negative electrode active material layer 21 includes a first negative electrode active material layer 21a and a second negative electrode active material layer 21b respectively arranged on the third surface 23 and the fourth surface 24.
[0049] By way of example only, the negative electrode current collector 22 may be a strip of metal foil, and its active material layer may include a negative electrode active material capable of reversibly absorbing and releasing charge carriers, a binder, a dispersant, and various additives.
[0050] By way of example only, the metal foil mentioned in the above-mentioned negative electrode sheet 20 may be copper foil, the negative electrode active material mentioned may include one or more of graphite, soft carbon, hard carbon, intermediate phase microspheres, and silicon-based materials, the binder mentioned may be a rubber such as styrene-butadiene rubber, and the dispersant mentioned may be a cellulose such as carboxymethyl cellulose.
[0051] The separator 30 is a member for insulating the positive electrode sheet 10 and the negative electrode sheet 20. As some examples, the separator 30 can be a porous belt made of a polyolefin resin such as polyethylene or polypropylene. Of course, other materials for the separator 30 are also foreseeable, and this application does not limit this, that is, no special requirements are made.
[0052] refer to Figure 4 and Figure 5 The positive electrode sheet 10 may include a positive electrode current collector 12 and a positive electrode active material layer 11. Along a first direction, that is, the Y direction shown in the figure, the positive electrode current collector 12 may have a first surface 19a and a second surface 19b that are arranged opposite to each other, for example Figure 5 The upper surface and the lower surface of the positive electrode sheet 10 described in the figure.
[0053] In the wound electrode body, the first surface 19a of the positive electrode collector 12 faces the winding center of the wound electrode body, and the second surface 19b is away from the winding center, that is, the first surface 19a is the inner circle of the positive electrode sheet 10, and the second surface 19b is the outer circle of the positive electrode sheet 10. Here, the winding center refers to the winding axis EE of the wound electrode body.
[0054] Continue to refer Figure 4 and Figure 5, along the second direction X, the first surface 19a may be provided with a first pasted area 14 and a first empty foil area 16 located at the tail of the positive current collector 12, and the second surface 19b may be provided with a second pasted area 15 and a second empty foil area 17 located at the tail of the positive current collector 12. The first pasted area 14 and the second pasted area 15 are provided with positive electrode active material layers 11, namely, the first positive electrode active material layer 11a and the second positive electrode active material layer 11b, respectively. The length of the first pasted area 14 may be greater than the length of the second pasted area 15, and the length of the first empty foil area 16 may be less than the length of the second empty foil area 17.
[0055] It can be understood that the first empty foil area 16 is a portion of the first surface 19a where the positive polarity material layer 11 is not provided, and the second empty foil area 17 is a portion of the second surface 19b where the positive electrode active material layer 11 is not provided. It should be noted that although the first empty foil area 16 and the second empty foil area 17 are not provided with the positive electrode active material layer 11, it does not mean that the positive electrode current collector 12 is directly exposed in the first empty foil area 16 and the second empty foil area 17.
[0056] Positive electrode active material layers 11 are respectively disposed on the first paste coating area 14 and the second paste coating area 15 . The positive electrode active material layers 11 include positive electrode active materials.
[0057] The positive electrode active material can be Li[Ni x Co y Mn z M 1-x-y-z ]O2 ternary material, 1-xyz>0. Here, M is a doping element in the ternary material, which is used to improve the stability of the ternary material. Exemplarily, M may include at least one of B, Al, Zr, W, Ta, Nb, Ti, Fe, Y, Ga, Cu, Zn, Ge, Mo, V and Cr.
[0058] By doping metal elements into the ternary material positive active material of the positive electrode active material layer 11, the structural stability of the ternary material can be improved, and the H2-H3 phase change during the insertion / deinsertion of lithium during the charge and discharge process, which causes the battery 1000 cycle capacity decay and side reactions, can be reduced. The swelling of the termination gel can be slowed down and the lithium precipitation caused by it can be reduced, thereby reducing the performance decline of the battery 1000.
[0059] In addition, the positive electrode active material layer 11 may further include one or more of a binder, a conductive agent, and a solvent.
[0060] For example, the binder may include one or more of polyvinylidene fluoride, polytetrachloroethylene, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyimide or polyethylene.
[0061] Illustratively, the conductive agent may include one or more of conductive ceramics, carbon black, graphite, graphene, polyaniline, polypyrrole, Ketjen black, acetylene black, and carbon nanotubes.
[0062] Illustratively, the solvent may include one or more of N-methylpyrrolidone, water, ethanol and polyethylene glycol.
[0063] By way of example only, the positive electrode current collector 12 may be a strip of metal foil, such as aluminum foil.
[0064] Continue to refer Figure 5 , at least part of the first empty foil area 16 is provided with a first stop glue 18a. The distance between the side of the first stop glue 18a close to the first paste area 14 and the edge of the first paste area 14 close to the first stop glue 18a (the edge opposite to the aforementioned side) can be d1. Here, d1≥0. That is, the first stop glue 18a does not cover the positive electrode active material layer 11.
[0065] In this way, the side edge of the first stop glue 18a disposed on the first empty foil area 16 just contacts or maintains a certain distance from the edge of the first positive electrode active material layer 14 close to the first stop glue 18a on the first paste coating area 16. Thus, the first empty foil area 16 of the positive electrode sheet 10 can be prevented from directly contacting the negative electrode sheet 20 to cause a short circuit.
[0066] At the same time, it can further improve and avoid the high-valence Ni (nickel) in the positive electrode active material of the ternary material and the electrolyte producing a series of side reactions during the recycling process of the lithium-ion battery, which makes the edge of the first termination glue 18a easy to swell, resulting in some lithium ions (Li+) in the first positive electrode active material layer 11 in the area covered by the first termination glue 18a diffusing to the edge of the first termination glue 18a. Furthermore, it can reduce and avoid the lithium ion concentration at the edge of the termination glue 18 being higher than the rest of the positive electrode active material layer, resulting in a local CB value becoming smaller and causing local lithium precipitation, further improving the performance of the battery 1000.
[0067] It should be noted that d1 is the distance between the position of the edge of the first stop glue 18a closest to the first paste area 14 on the side of the first stop glue 18a close to the first paste area 14 and the edge of the first paste area 14. It can be understood that the side of the first stop glue 18a close to the first paste area 14 may not be parallel to the first edge of the first paste area 14. In addition, the edge of the first paste area 14 close to the first stop glue 18a and the side of the first stop glue 18a close to the first paste area 14 may be irregular lines, such as oblique lines, fold lines or wavy lines.
[0068] Continue to refer Figure 4 and Figure 5, at least part of the second empty foil area 17 is provided with a second stop glue 18b. The distance between the side of the second stop glue 18b close to the second paste area 15 and the edge of the second paste area 15 close to the second stop glue 18b (the edge opposite to the aforementioned side) can be d2, d2 ≥ 0. That is, the second stop glue 18b does not cover the second positive electrode active material layer 11b.
[0069] In this way, the side of the second stopper glue 18b attached to the second empty foil area 17 just contacts or keeps a certain distance from the edge of the second stopper glue 18b of the second positive electrode active material layer 11b disposed on the second paste coating area 15. Thus, the second empty foil area 17 can be prevented from directly contacting the negative electrode sheet 20 to cause a short circuit.
[0070] At the same time, it further improves and avoids the high-valence Ni (nickel) in the ternary material positive electrode active material and the electrolyte producing a series of side reactions during the recycling process of the lithium-ion battery, which makes the edge of the second termination glue 18b easy to swell, resulting in some lithium ions (Li+) in the second positive electrode active material layer 11b in the area covered by the second termination glue 18b diffusing to the edge of the second termination glue 18b. In addition, it can reduce and avoid the lithium ion concentration at the edge of the second termination glue 18b being higher than the rest of the second positive electrode active material layer 11b, resulting in a local CB value becoming smaller and causing local lithium precipitation, further improving the performance of the battery 1000.
[0071] It should be noted that d2 is the distance between the position of the edge of the second stop glue 18b closest to the second paste area 15 on the side of the second stop glue 18b close to the second paste area 15 and the edge of the second paste area 15 (the edge opposite to the aforementioned side). It can be understood that the side of the second stop glue 18b close to the second paste area 15 may not be parallel to the edge of the second stop glue 18b close to the second paste area 15, and the first edge of the second paste area 15 and the side of the second stop glue 18b close to the second paste area 15 may be irregular lines, such as oblique lines, fold lines or wavy lines.
[0072] The units of the above d1 and d2 may be mm.
[0073] Next reference Figure 5, in some embodiments, d1 may satisfy: 0<d1≤A / (B1*2). In addition, d2 may satisfy 0<d2≤A / (B2*2). That is to say, along the extension direction of the positive electrode sheet 10, the termination glue 18 does not contact the positive electrode active material layer 11. Here, A is the single-sided paste thickness of the positive electrode sheet 10, and B1 and B2 are the thicknesses of the first termination glue 18a and the second termination glue 18b, respectively. It should be noted that when the single-sided paste thickness on both sides of the positive electrode sheet is different, A is the average, minimum or maximum value of the paste thickness on both sides, and this application does not limit this. It should be noted that B1 and B2 may be equal or unequal, and d1 and d2 may be equal or unequal, and this application does not limit this.
[0074] Controlling d1 and d2 within this range can improve and avoid a series of side reactions between the high-valence Ni (nickel) in the positive active material of the ternary material and the electrolyte during the recycling of the lithium-ion battery, which makes the edge of the termination glue 18 prone to swelling, resulting in some lithium ions (Li+) in the positive active material layer 11 in the area covered by the termination glue 18 diffusing to the edge of the termination glue 18. Furthermore, it can reduce and avoid the lithium ion concentration at the edge of the termination glue 18 being higher than that in the rest of the positive active material layer 11, resulting in a local CB value becoming smaller and causing local lithium precipitation, further improving the performance of the battery 1000. In addition, while avoiding the positive current collector 12 from contacting the negative electrode sheet 20 to cause a short circuit, the termination glue 18 can be kept at an appropriate distance from the positive active material layer 11, and it is convenient for operation and process implementation.
[0075] A can be 30μm to 100μm (for example, 35μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 95μm, etc.). Preferably, A is 50μm to 80μm. B1 and B2 can be 15μm to 30μm, respectively (for example, 17μm, 19μm, 21μm, 23μm, 25μm, 27μm, 29μm, etc.), preferably, B1 and B2 can be 20μm to 25μm. In this way, the lithium ion concentration at the edge of the termination glue 18 is higher than that in the rest of the positive electrode active material layer 11, which causes the local CB value to become smaller and produces local lithium precipitation, further improving the performance of the battery 1000. At the same time, the distance between the termination glue 18 and the positive electrode active material layer 11 can be adapted to the thickness of the positive electrode active material layer 11 and the thickness of the termination glue 18, so as to avoid excessive local thickness differences in the battery cell, reduce the surface flatness of the battery cell, affect the battery performance, and further facilitate operation and process implementation.
[0076] Exemplarily, the stop glue 18 may be composed of a substrate and a glue layer. For example, the substrate may be a PET film or a BOPP film material, and the glue layer may be an acrylic pressure-sensitive adhesive or rubber.
[0077] Continue to refer Figure 5 In some examples, a fillet or chamfer is provided at the end of the first positive active material layer 11a near the first termination glue 18a, that is, at one end of the first paste coating area 14 near the first empty foil area 16, the first positive active material layer 11a can be provided with a fillet R or a chamfer.
[0078] Continue to refer Figure 5 In some examples, a fillet or chamfer is provided at the end of the second positive electrode active material layer 11b near the second termination glue 18b, that is, at one end of the second paste coating area 15 near the second empty foil area 17, the second positive electrode active material layer 11b can be provided with a fillet R or a chamfer.
[0079] During use, the battery cell will expand, and the stress generated after the expansion will be transmitted layer by layer and superimposed on the positive electrode sheet 10 at the tail of the battery cell. This position is at a greater risk of breaking or falling powder during expansion. Performing an R angle or chamfer design treatment at the end of the positive active layer 11 can prevent the sharp corners of the positive active material layer 11 from falling powder, thereby avoiding the problem of poor K value of the battery caused by dust and foreign matter, and further avoiding dust and foreign matter from piercing the diaphragm 30 and contacting the negative electrode to cause a short circuit. At the same time, the positive active material layer 11 at the edge of the positive electrode sheet adopts an R angle or chamfer design, which can also alleviate the thickness difference between the two sides of the positive electrode sheet 10 and the stress concentration caused by expansion, avoid stress concentration on one line, and thus improve the cracking or even breaking of the electrode sheet at this position caused by the expansion of the battery cell during the cycle, thereby improving the cycle performance of the battery.
[0080] In some examples, a fillet R or chamfer can be provided at both the end of the first positive electrode active layer 11a near the first termination glue 18a and the end of the second positive electrode active layer 11b near the second termination glue 18b. Accordingly, the above-mentioned effects can be better achieved, which will not be described in detail here.
[0081] Preferably, when the positive electrode active material layer is provided with a fillet R at the end of the first positive electrode active layer 11a near the first termination glue 18a and / or at the end of the second positive electrode active layer 11b near the second termination glue 18b, the radius of the fillet R is 1mm to 10mm (for example, 1.5mm, 2.5mm, 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm, etc.), so as to better avoid powder loss, and alleviate the stress concentration caused by the thickness difference and expansion difference between the two sides of the positive electrode sheet 10, and better improve the fracture of the electrode sheet. More preferably, the radius of the fillet R is 2mm to 6mm, so as to better avoid powder loss, alleviate the stress concentration caused by the thickness difference and expansion difference between the two sides of the positive electrode sheet 10, and thus better improve the fracture of the electrode sheet.
[0082] As mentioned above, in Li[Ni x Coy Mn z M 1-x-y-z ] In the O2 ternary material, 0.5≤x<1 (for example, 0.55, 0.60, 0.70, 0.80, 0.90, etc.), 0≤y≤0.2 (for example, 0.02, 0.05, 0.08, 0.10, 0.12, 0.14, 0.16, 0.18, etc.), 0≤z≤0.3 (for example, 0.05, 0.08, 0.10, 0.13, 0.15, 0.18, 0.20, 0.23, 0.25, 0.28, etc.). In this ternary material, Ni2+ mainly plays the role of supply capacity. The higher the nickel content, the higher the theoretical specific capacity. However, too high a nickel content will bring about the problem of cation mixing, resulting in a decrease in the performance of the battery 1000. Co3+ can improve the cyclability and rate performance of the material, but Co is expensive and Co ore is scarce. Controlling the cobalt content can save costs and protect resources. Therefore, by controlling the corresponding components in the ternary material within the above range, better battery 1000 performance can be obtained while taking into account the structural stability and cost of the ternary material.
[0083] Preferably, 0.8≤x<1, 0≤y≤0.1, 0≤z≤0.1. By controlling the corresponding components in the ternary material within this range, better performance of the battery 1000 can be further obtained while better considering the structural stability and cost of the ternary material.
[0084] In one embodiment, the ternary material mentioned above can be a single crystal, that is, the ternary material exists in the form of a single crystal. When the ternary material is a single crystal, there is no grain boundary inside the single crystal ternary positive electrode material, which can avoid the degradation of material performance caused by grain boundary crushing, and the power performance is better. However, the manufacturing cost of the single crystal is high, and the surface density of the positive electrode active material layer 11 is low.
[0085] In another embodiment, the ternary material mentioned above may also be a mixture of single crystal and polycrystalline, that is, the ternary material exists in the form of a mixture of single crystal and polycrystalline. Compared with the ternary material being a single crystal or a polycrystalline, the ternary material being a mixture of single crystal and polycrystalline can take into account both the cost and the power performance of the battery 1000, while appropriately alleviating the material performance degradation caused by the grain boundary crushing of the polycrystalline, thereby improving the performance of the battery 1000.
[0086] When the ternary material is a mixture of single crystal and polycrystalline, the mass percentage of single crystal in the positive electrode active material can be 50% to 100% (e.g., 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, etc.), and the mass percentage of polycrystalline can be 0% to 50% (e.g., 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, etc.). In this way, cost and power performance can be better balanced, while appropriately alleviating the degradation of material performance caused by polycrystalline grain boundary crushing, thereby improving the performance of the battery 1000.
[0087] Preferably, the mass percentage of single crystal in the positive electrode active material can be 80% to 100%, and the mass percentage of polycrystalline can be 0% to 20%. In this way, the cost and power performance can be better balanced, and the degradation of material performance caused by polycrystalline grain boundary crushing can be appropriately alleviated, thereby improving the performance of the battery 1000.
[0088] In some examples, the specific surface area of the ternary material can be 0.5 m 2 / g~1.5m 2 / g (e.g. 0.7m 2 / g,0.9m 2 / g, 1.1m 2 / g, 1.3m 2 / g, etc.). The larger the specific surface area of the ternary material, the better the electrolyte infiltration effect, the faster the lithium insertion speed of the ternary material, and the better the electrolyte conductivity. However, too high a specific surface area will also increase the contact area between the positive electrode active material and the electrolyte, aggravate the side reaction between the positive electrode active material and the electrolyte, and cause the battery 1000 to deteriorate in performance. The specific surface area of the ternary material is obtained by a specific surface area analyzer (BET) test.
[0089] Therefore, controlling the specific surface area of the ternary material within this range can take into account both the conductivity of the electrolyte and the control of the side reactions of the positive electrode active material, thereby obtaining better battery 1000 performance. Preferably, the specific surface area of the ternary material can be 0.8 m 2 / g~1.2m 2 / g (e.g. 0.85m 2 / g,0.95m 2 / g,1.0m 2 / g, 1.2m 2 / g, etc.). Within the preferred range, the conductivity of the electrolyte can be better taken into account and the side reactions of the positive electrode active material can be controlled, thereby obtaining better performance of the battery 1000.
[0090] In some embodiments, the particle size of the ternary material can also be controlled. For example, the particle size of the ternary material D 50It can be 2 μm to 12 μm (e.g. 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, etc.), that is, the particle size value corresponding to the ternary material when the cumulative distribution percentage reaches 50%. max It can be 15 μm to 25 μm (e.g. 17 μm, 19 μm, 21 μm, 23 μm, etc.), D max That is, the maximum particle size of the ternary material. 50 and D max It can be tested by laser particle size analyzer.
[0091] Controlling the particle size of the ternary material within the above range can take into account the dynamics of the material and prevent the gaps between the positive electrode active materials in the first paste coating area 14 with a smaller surface density from being too large, thereby increasing side reactions with the electrolyte and worsening gas production.
[0092] In the design of the battery cell, it is usually required that the N / P ratio is greater than 1 to ensure that the reversible capacity of the negative electrode is greater than the reversible capacity of the positive electrode during the cycle use of the battery 1000. In this way, it is possible to minimize and avoid the deposition of excess lithium ions on the negative electrode surface to form lithium dendrites that reduce the performance of the battery 1000 or puncture the diaphragm 30, thereby ensuring the normal performance and safety of the battery 1000.
[0093] However, for a wound electrode body, the curvatures of the inner and outer circles of the electrode sheet are inconsistent at the curved portion 101, with the inner circle having a larger curvature and the outer circle having a smaller curvature. Therefore, the N / P ratios of the inner and outer circles of the electrode sheet are inconsistent. If the design is not appropriate, lithium deposition is likely to occur at the curved portion 101.
[0094] At present, there is no better method in the industry to deal with the N / P ratio at the curved surface structure. For example, if the N / P ratio of the inner circle of the negative electrode sheet 20 corresponding to the outer circle of the positive electrode sheet 10 is greater than 1, the N / P ratio of the battery cell will be designed. At this time, the N / P ratio of the inner circle of the positive electrode sheet 10 corresponding to the outer circle of the negative electrode sheet 20 will be insufficient, and the battery cell is prone to lithium deposition at the outer circle of the negative electrode sheet 20 with a curved surface structure, thereby affecting the cycle life and safety of the battery cell. Therefore, it is necessary to improve the N / P ratio here. In order to solve this problem, the industry now basically adopts an interference N / P ratio design to ensure that the N / P ratio of the inner and outer circles is sufficient. However, this method will cause the N / P ratio of the outer circle of the positive electrode sheet 10 to be too large, which will reduce the initial efficiency of the battery 1000 and reduce the energy density of the battery 1000.
[0095] In order to improve the N / P ratio distribution at the bend 101, in some embodiments, at least at the bend 101, the surface density of the first positive electrode active material layer 11 in the first paste coating area 14 may be less than the surface density of the second positive electrode active material layer 11 in the second paste coating area 15. The surface density of the active material in the paste coating area of the first surface 19a is relatively small, which can increase the N / P ratio of the inner circle of the positive electrode sheet 10 corresponding to the outer circle of the negative electrode sheet 20. In this way, it is equivalent to reducing the amount of positive electrode active material, which can reduce the release of lithium ions from the positive electrode, so that the negative electrode has enough space to accommodate the lithium ions released from the positive electrode, thereby reducing the risk of lithium deposition of the negative electrode sheet 20 at this location.
[0096] Preferably, at least in the curved portion 101, the surface density of the positive electrode active material layer 11 in the first pasted area 14 is 90% to 99% of the surface density of the positive electrode active material layer 11 in the second pasted area 15, such as 91%, 93%, 95%, or 98%. Within this range, the energy density and the N / P ratio can be well balanced, and the risk of lithium deposition in the outer ring of the negative electrode sheet 20 can be reduced while obtaining better performance of the battery 1000.
[0097] More preferably, at least in the curved portion 101, the surface density of the positive electrode active material layer 11 in the first pasted area 14 is 94% to 97% of the surface density of the positive electrode active material layer 11 in the second pasted area 15. Within this range, the energy density and the N / P ratio can be better balanced, and the risk of lithium deposition in the outer ring of the negative electrode sheet 20 can be reduced while obtaining better performance of the battery 1000.
[0098] In some examples, at least in the curved portion 101, the thickness of the first positive electrode active material layer 11a is h1, the thickness of the second positive electrode active material layer 11b is h2, and h1<h2. In this way, the energy density and the N / P ratio can be well balanced, and the risk of lithium deposition in the outer ring of the negative electrode sheet 20 can be reduced while obtaining better performance of the battery 1000.
[0099] In some embodiments, at least in the curved portion 101, the N / P ratio of the second negative electrode active material layer 21b to the first positive electrode active material layer 11a is greater than the N / P ratio of the first negative electrode active material layer 21a to the second positive electrode active material layer 11b, and the difference between the two is 0.005-0.2, such as 0.01, 0.03, 0.05, 0.08, 0.1, 0.12, 0.15 or 0.18. The N / P ratio of the corresponding positions on both sides of the positive electrode sheet 10 is set within this range. On the one hand, it can ensure that the N / P ratio of the corresponding position of the first paste coating area 14 of the first surface 19a of the positive electrode sheet 10 is sufficient, which can reduce and avoid the occurrence of lithium deposition in the outer circle of the negative electrode sheet 20; on the other hand, it is not necessary to increase the N / P ratio of the corresponding position of the second paste coating area 15 of the second surface 19b of the positive electrode sheet 10, which is conducive to improving the overall energy density of the battery 1000.
[0100] Preferably, the difference between the two is 0.02 to 0.08. Within this range, the N / P ratio and the energy density of the battery 1000 can be better balanced.
[0101] In some embodiments, at the curved portion 101, the positive electrode active material layer 11 of the first paste coating area 14 is provided with holes or concave textures (not shown in the figure), so as to reduce the positive electrode active material in the first paste coating area 14 through the holes or concave textures, thereby improving the negative electrode and positive electrode N / P ratio at the corresponding position of the first paste coating area 14, thereby reducing and avoiding lithium precipitation in the outer circle of the negative electrode. In addition, the holes and concave textures can also store electrolyte, which is conducive to the transmission of lithium ions.
[0102] It can be understood that the texture structure of holes or depressions can be formed by mechanical pores, laser pores or rolling on the positive electrode active material layer 11, or can be formed when the positive electrode active material layer 11 is formed. The holes or depressions can penetrate the positive electrode sheet along the thickness direction of the electrode sheet, or they may not penetrate the positive electrode sheet. This application does not limit this.
[0103] In some examples, for ease of processing, the surface density and thickness, N / P ratio, and the arrangement and characteristics of the texture structure of pores or depressions of the positive electrode active material layer 11 may be provided in both the flat portion 102 and the curved portion 101 .
[0104] In the present application, the wound electrode body 100 may be a conventional wound electrode body. Preferably, the wound electrode body 100 is a multi-electrode tab 13 structure.
[0105] Combine the following Figures 2 to 6 , the wound electrode body 100 of the present application is illustrated by way of example. Figures 2 to 6 As shown, the wound electrode body 100 includes a positive electrode sheet 10 , a negative electrode sheet 20 , and a separator 30 which are stacked.
[0106] like Figure 4 and Figure 5 As shown, the positive electrode current collector 12 of the positive electrode sheet 10 has a first surface 19a and a second surface 19b arranged opposite to each other. The first surface 19a is provided with a first paste area 14 and a first empty foil area 16, and the second surface 19b is provided with a second paste area 15 and a second empty foil area 17. The first empty foil area 16 can be pasted with a first stop glue 18a, and the second empty foil area 17 can be pasted with a second stop glue 18b. The distance between the side of the first stop glue 18a close to the first paste area 14 and the first edge of the first paste area 14 is d1, and the distance between the side of the second stop glue 18b close to the second paste area 15 and the first edge of the second paste area 15 is d2, and d1 satisfies: 0<d1≤A / (B*2), and d2 satisfies 0<d2≤A / (B*2). A is 50μm~80μm; B is 20μm~25μm.
[0107] In this way, the termination glue 18 maintains an appropriate distance from the positive electrode active material layer 11, which can avoid the reduction of the CB value in this area caused by the accumulation of lithium ions at the edge of the termination glue 18, thereby avoiding the lithium precipitation caused by this, and at the same time avoiding the positive electrode current collector 12 from contacting the negative electrode sheet 20 to cause a short circuit.
[0108] like Figure 2 As shown, at the end of the first pasting area 14 and the second pasting area 15, the positive electrode active material layer 11 is provided with a fillet R, and the radius of the fillet R is 2 mm to 6 mm to relieve stress concentration and avoid stress concentration on one line to cause tape breakage.
[0109] In the ternary material, 0.8≤x<1, 0≤y≤0.1, 0≤z≤0.1. M includes at least one of B, Al, Zr, W, Ta, Nb, Ti, Fe, Y, Ga, Cu, Zn, Ge, Mo, V and Cr. The ternary material is a mixture of single crystal and polycrystal, with the mass percentage of single crystal being 80% to 100% and the mass percentage of polycrystal being 0 to 20%.
[0110] The specific surface area of the ternary material is 0.8m 2 / g~1.2m 2 / g. D of ternary materials 50 2μm~12μm, D max The compaction density of the positive electrode active material layer 11 is 3.0 g / cm 3 ~3.5g / cm 3 , surface density is 12mg / cm 2 ~25mg / cm 2 The surface resistance of the positive electrode sheet 10 is 150 mΩ to 300 mΩ.
[0111] By controlling the composition and structure of the ternary material, the density of the positive electrode active material layer 11 and the surface resistance of the positive electrode sheet 10, etc., better battery performance can be obtained.
[0112] The positive electrode active material layer 11 mentioned above may have a compaction density of 3.0 g / cm 3 ~3.5g / cm 3 (e.g. 3.1 g / cm 3 , 3.2g / cm 3 , 3.4g / cm 3 In addition, the surface density of the positive electrode active material layer 11 can be 12 mg / cm 2 ~25mg / cm 2 (e.g. 14 mg / cm 2 , 16mg / cm 2 , 18mg / cm 2, 20mg / cm 2 , 22mg / cm 2 , 24mg / cm 2 Etc.). Setting the surface density and compaction density of the positive electrode sheet 10 within the above range can take into account the energy density and performance of the battery cell as a whole, and can also prevent the process instability and easy breakage caused by the large difference in thickness between the first paste area 14 and the second paste area 15 of the positive electrode sheet 10. Especially at high charge and discharge rates, local expansion may cause rupture of the battery structure or leakage of the electrolyte. The surface density is calculated by weighing the electrode sheet after coating. The specific test method is to disassemble the battery, take out the positive electrode sheet 10, and sample the single-sided coating area of the positive electrode where only the first surface 19a of the positive electrode sheet 10 has the first paste area 14. The sampled sample is recorded as A, and the sample is a circle with a diameter of 12 mm, and then weighed as A1. After wiping off all the paste on the surface of the sampled sample A (which can be removed by immersion in an organic solvent or by washing, which is not limited here), weigh it as A2. It can be understood that A2 is the weight of the positive electrode collector 12 of the sampled sample A. The surface density of the first positive electrode active material layer 11a = (A1-A2) / circular area; It should be noted that the number of samples can be 1 or greater than or equal to 2, and the sampling positions can be evenly distributed on the electrode sheet, which is not limited here. When the number of samples is greater than or equal to 2, when calculating the weight, the average weight of all sampled samples A should be calculated. Similarly, when calculating the weight A2 of the positive electrode current collector, the average weight of all positive electrode current collectors should also be taken. The overlapping area of the first paste coating area 14 and the second paste coating area 15 of the positive electrode sheet 10, that is, the position of the double-sided paste coating area of the positive electrode sheet 10, is sampled, and the sampled sample is recorded as B. The sampled samples B are all circular with a diameter of 12 mm, and then their weight is weighed as B1. The number of samples B can be 1 or greater than or equal to 2, and the sampling positions can be evenly distributed on the positive electrode sheet 10, which is not limited here. When the number of samples is greater than or equal to 2, the method for calculating the weight is as described above, and it will not be repeated here. The surface density of the second positive electrode active material layer 11b = (B1-A2) / area-the surface density of the first positive electrode active material layer 11a. The compaction density is calculated by the surface density and the thickness of the pole piece. The thickness of the pole piece can be obtained by scanning electron microscope or micrometer test. The compaction density is calculated by the surface density and the thickness of the pole piece.
[0113] In some embodiments, the thickness of the positive active material layer 11 on the first surface 19a of the positive current collector 12 is h1, and the thickness of the positive active material layer 11 on the second surface 19b is h2, where h1<h2, so as to adjust the N / P ratio of the positive and negative electrodes.
[0114] Here, the N / P (Negative / Positive) ratio (hereinafter referred to as N / P ratio) refers to the ratio of the actual capacity of the positive and negative electrode materials per unit area, and its calculation formula is: gram capacity of negative electrode active material × negative electrode surface density × negative electrode active material content ratio ÷ (gram capacity of positive electrode active material × positive electrode surface density × positive electrode active material content ratio).
[0115] In addition, the surface resistance of the positive electrode sheet 10 can be 150mΩ to 300mΩ (e.g., 170mΩ, 190mΩ, 210mΩ, 230mΩ, 250mΩ, 270mΩ, 290mΩ, etc.) to ensure the charge and discharge performance of the battery 1000. The surface resistance can be tested using an automatic lithium battery electrode sheet resistance tester.
[0116] Exemplary Battery 1000
[0117] On the other hand, Figure 6 and 7 As shown, the embodiment of the present application further provides a battery 1000. The battery 1000 includes the wound electrode body 100 described above.
[0118] refer to Figure 6 and Figure 7 The battery 1000 may include a wound electrode body 100 and a housing 200. The housing 200 may be provided with a receiving cavity, and one or more wound electrode bodies 100 may be received in the receiving cavity.
[0119] like Figure 7 As shown, the housing 200 may be square, for example. That is, the battery 1000 may be a square battery 1000. The material of the housing 200 may be the same as that used in the past, and there is no particular limitation. For example, the housing 200 may be made of metal, in particular, may be made of aluminum (alloy) or iron (alloy).
[0120] like Figure 8 As shown, illustratively, the housing 200 is flat and made of a relatively soft material, such as an aluminum-plastic film. That is, in this embodiment, the battery 1000 can be a soft-pack battery 1000.
[0121] It is foreseeable that in other examples of the embodiments of the present application, the battery 1000 may also be implemented as other types besides the square battery 1000 and the soft-pack battery 1000 .
[0122] It should be noted that other aspects of the structure of the battery 1000 may be the same as the structure of the conventional battery 1000 , and for the purpose of brevity, this embodiment of the present application will not be described in detail.
[0123] The battery 1000 can be made into a wound electrode body by making the positive electrode sheet 10, the negative electrode sheet 20 and the separator 30 according to a conventional winding structure, and then the battery 1000 is made through steps such as packaging, liquid injection, formation, secondary sealing and capacity division. The electrolyte is a conventional commercial electrolyte, and this application does not make any special requirements for this.
[0124] The battery 1000 provided according to the embodiment of the present application has the corresponding effects of the above-mentioned wound electrode body 100 , and the details are referred to above and will not be repeated here.
[0125] The battery 1000 provided in the embodiment of the present application can be used to prepare a battery 1000 with a central tab process (CTP). Of course, the tabs of the battery 1000 of the present application can also be set in other forms, and the present application does not limit this.
[0126] It should be noted that in the present disclosure, "battery 1000" refers to a power storage device that can be repeatedly charged and discharged, which can be interpreted as the concept of "secondary battery 1000". In the embodiment of the present application, the concept of "secondary battery 1000" can include lithium-ion secondary battery 1000 and the like.
[0127] The present application is described in detail below in conjunction with specific embodiments, which are used to understand rather than limit the present application.
[0128] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources. The processing procedures and techniques involved are conventional technical means unless otherwise specified.
[0129] Example 1
[0130] Preparation of negative electrode sheet 20: Disperse the negative electrode active material, sodium carboxymethyl cellulose, styrene butadiene rubber and conductive carbon black in a solvent deionized water (or water) in a mass percentage of 93:2.5:1.5:3, and mix them evenly to obtain a slurry. The prepared negative electrode slurry is evenly coated on a copper foil, dried at 100°C, and rolled and cut to obtain a negative electrode sheet 20. The negative electrode active material is a carbon-coated artificial graphite material, wherein the D50 of the graphite material is 12μm and the specific surface area is 1.2m 2 / g, and the compaction density of the negative electrode active material layer 21 is 1.7 g / cm 3 , surface density is 12mg / cm 2 The thickness of the negative electrode active material layer 21 was 70.5 μm.
[0131] Preparation of positive electrode sheet 10: The positive electrode active material Li[Ni 0.83 Co 0.06 Mn 0.05 Fe 0.06]O2 ternary material, binder polyvinylidene fluoride, and conductive agent carbon black are mixed in a mass percentage ratio of 90:5:5, and an appropriate amount of N-methylpyrrolidone is added as a solvent. The electrode slurry is evenly coated on the aluminum foil, and rolled and cut to form a positive electrode sheet 10. The compaction density of the positive active material layer 11 on the first surface 19a of the positive electrode sheet is 3.1g / cm 3 , surface density is 19.8mg / cm 2 The surface density of the positive electrode active material layer 11 on the second surface 19b is 20.5 mg / cm 2 , the surface density of the positive electrode active material layer 11 on the first surface 19a is 96.59% of the surface density of the positive electrode active material layer 11 on the second surface 19b, and the surface density is controlled by controlling the amount of coating slurry. The thickness of the positive electrode active material layer 11 on the first surface 19a is 63.6μm, and the thickness of the positive electrode active material layer 11 on the second surface 19b is 66.3μm. According to the weight of active material per unit area of the positive electrode sheet 10 and the negative electrode sheet 20, the N / P ratio of the second negative electrode active material layer 21b to the first positive electrode active material layer 11a is calculated to be 1.12, and the N / P ratio of the first negative electrode active material layer 21a to the second positive electrode active material layer 11b is calculated to be 1.08, and the difference between the two is 0.04.
[0132] In the ternary material, the single crystal is 87.3wt% and the polycrystalline is 12.7wt%. The ternary material mixture is obtained by mixing the single crystal material and the polycrystalline material in a mass ratio of 87.3:12.7, and the mixture accounts for 90wt% of the total mass of the positive electrode active material of the lithium-ion battery. The specific surface area of the ternary material is 0.95m 2 / g. D of ternary materials 50 The D of the ternary material is 6μm. max The surface resistance of the positive electrode sheet 10 is 178 mΩ. The thickness B of the termination glue 18 is 22 μm, and the spacing d1 and d2 between the termination glue 18 and the positive electrode active material layer 11 are 1.36 mm. The fillet R of the positive electrode active material layer 11 at the end of the first paste coating area 14 and the second paste coating area 15 is R4.8 mm.
[0133] Then, according to the conventional winding structure, the positive electrode sheet 10, the negative electrode sheet 20 and the separator 30 are made into a wound battery 1000, and then the battery 1000 is made through the steps of packaging, liquid injection, formation, secondary sealing, and capacity division. Here, the electrolyte is a conventional commercially available electrolyte.
[0134] Example 2 Group
[0135] This group of embodiments is used to illustrate the impact of changes in d1 and d2.
[0136] Example 2a
[0137] The difference between Example 2a and Example 1 is that the surface density of the first positive electrode active material layer 11a and the second positive electrode active material layer 11b is the same, both of which are 19.8 mg / cm 2 , and the thickness A is the same, both are 63.6μm. According to the weight of active material per unit area of the positive electrode sheet 10 and the negative electrode sheet 20, the N / P ratio of the second negative electrode active material layer 21b to the first positive electrode active material layer 11a is calculated to be 1.12, and the N / P ratio of the first negative electrode active material layer 21a to the second positive electrode active material layer 11b is calculated to be 1.12, and the difference between the two is 0.
[0138] Example 2b
[0139] This embodiment is carried out with reference to the embodiment 1, except that d1 and d2 are 0.12 mm.
[0140] Example 2c
[0141] This embodiment is carried out with reference to the embodiment 1, except that d2 is 1.36 mm, and the first stop glue 18 b covers the first positive electrode active material layer 11 b .
[0142] Example 2d
[0143] This embodiment is carried out with reference to the embodiment 1, except that d1 and d2 are 4.0 mm.
[0144] Example 3 Group
[0145] This group of examples is used to illustrate the impact of changes in the ratio of elements in the ternary material. When the ratio of different elements in the positive electrode active material changes, the corresponding material gram capacity will change. In order to ensure the same N / P ratio as in Example 1, the surface density of the positive electrode active material layer 11 is adjusted accordingly.
[0146] Example 3a
[0147] This embodiment is carried out with reference to the embodiment 1, except that the positive electrode active material is Li[Ni 0.53 Co 0.19 Mn 0.23 Fe 0.05 The surface density of the positive electrode active material layer 11 on the first surface 19a of the positive electrode sheet is 22.51 mg / cm 2 The surface density of the positive electrode active material layer 11 on the second surface 19b is 23.34 mg / cm 2 The thickness of the positive electrode active material layer 11 on the first surface 19 a is 72 μm, and the thickness of the positive electrode active material layer 11 on the second surface 19 b is 75 μm.
[0148] Example 3b
[0149] This embodiment is carried out with reference to the embodiment 1, except that the positive electrode active material is Li[Ni 0.93 Co 0.01 Mn 0.05 Fe 0.01 The surface density of the positive electrode active material layer 11 on the first surface 19a of the positive electrode sheet is 19.21 mg / cm 2 The surface density of the positive electrode active material layer 11 on the second surface 19b is 19.92 mg / cm 2 The thickness of the positive electrode active material layer 11 on the first surface 19 a is 61.2 μm, and the thickness of the positive electrode active material layer 11 on the second surface 19 b is 63.8 μm.
[0150] Example 4 Group
[0151] This group of embodiments is used to illustrate the influence of the change of the fillet R of the positive electrode active material layer 11 at the end of the first paste coating area 14 and the second paste coating area 15 .
[0152] Example 4a
[0153] This embodiment is carried out with reference to the embodiment 1, except that the positive electrode active material layer 11 is not provided with a rounded corner R at the end of the first paste coating area 14 and the second paste coating area 15 .
[0154] Example 4b
[0155] This embodiment is carried out with reference to the embodiment 1, except that at the end of the first paste coating area 14 and the second paste coating area 15, the radius of the fillet R of the positive electrode active material layer 11 is 8 mm.
[0156] Example 5 Group
[0157] This group of embodiments is used to illustrate the impact of changes in the N / P ratio.
[0158] Example 5a
[0159] This embodiment is carried out with reference to the embodiment 1, except that the surface density of the positive active material layer 11 on the first surface 19a of the positive current collector 12 is 87.8% of the surface density of the positive active material layer 11 on the second surface 19b. The surface density of the positive active material layer 11 on the first surface 19a is 18.90 mg / cm 2 The surface density of the positive electrode active material layer 11 on the second surface 19b is 21.52 mg / cm 2 The thickness of the positive electrode active material layer 11 on the first surface 19a is 60.8 μm, and the thickness of the positive electrode active material layer 11 on the second surface 19b is 69.22 μm. The N / P ratio of the negative electrode and the positive electrode at the corresponding position of the first paste coating area is greater than the N / P ratio of the negative electrode and the positive electrode at the corresponding position of the second paste coating area, which is 0.14.
[0160] Example 5b
[0161] This embodiment is carried out with reference to the embodiment 1, except that the surface density of the positive active material layer 11 on the first surface 19a of the positive current collector 12 is 99.6% of the surface density of the positive active material layer 11 on the second surface 19b. The surface density of the positive active material layer 11 on the first surface 19a is 20.11 mg / cm 2 The surface density of the positive electrode active material layer 11 on the second surface 19b is 20.19 mg / cm 2 The thickness of the positive electrode active material layer 11 on the first surface 19a is 64.9 μm, and the thickness of the positive electrode active material layer 11 on the second surface 19b is 65.1 μm. The N / P ratio of the negative electrode and the positive electrode at the corresponding position of the first paste coating area is greater than the N / P ratio of the negative electrode and the positive electrode at the corresponding position of the second paste coating area, which is 0.0046.
[0162] Example 5c
[0163] This embodiment is carried out with reference to the embodiment 1, except that the surface density of the positive active material layer 11 on the first surface 19a of the positive current collector 12 is 87.5% of the surface density of the positive active material layer 11 on the second surface 19b. The surface density of the positive active material layer 11 on the first surface 19a is 18.9 mg / cm 2 The surface density of the positive electrode active material layer 11 on the second surface 19b is 21.6 mg / cm 2 The thickness of the positive electrode active material layer 11 on the first surface 19a is 70 μm, and the thickness of the positive electrode active material layer 11 on the second surface 19b is 80 μm. The N / P ratio of the negative electrode and the positive electrode at the corresponding position of the first paste coating area is greater than the N / P ratio of the negative electrode and the positive electrode at the corresponding position of the second paste coating area by 0.15.
[0164] Comparative Example 1
[0165] The difference from Example 1 is that the positive electrode active material is Li[Ni 0.83 Co 0.06 Mn 0.11 ]O2 ternary material.
[0166] Comparative Example 2
[0167] The difference from Example 1 is that the length of the first stop glue 18 a and the second stop glue 18 b covering the positive electrode active material layer 11 is 3.2 mm respectively.
[0168] Comparative Example 3
[0169] The difference from Example 1 is that the positive electrode active material is Li[Ni 0.83 Co 0.06 Mn 0.11]O2 ternary material, the length of the first termination glue 18a and the second termination glue 18b covering the positive electrode active material layer 11 is 3.4 mm respectively.
[0170] The batteries 1000 prepared in various embodiments and comparative examples were subjected to electrical performance tests.
[0171] Electrical performance test: Using a charging and discharging device, charge 10 batteries 1000 in each group of embodiments at a constant temperature of 25°C ± 3°C at a rate of 2C, and discharge the batteries 1000 at a rate of 2C. After 300 cycles in this way, determine the electrical performance (capacity retention rate, taking the average value of the 10 batteries 1000).
[0172] Battery cell abnormality test: Use charging and discharging equipment to charge 30 batteries 1000 in each example at a constant temperature of 25℃±3℃ at a rate of 2C, and discharge the batteries 1000 at a rate of 2C. Cycle in this way. Randomly take 10 battery cells from each example sample. After 300 cycles, disassemble and confirm the lithium plating and battery cell abnormality.
[0173] Determination of the degree of lithium deposition: No lithium deposition: After disassembly after 300T cycle, the surface of the negative electrode sheet is golden yellow; Slight lithium deposition: Gray-black areas appear locally on the surface of the negative electrode sheet, and the ratio of the lithium deposition area of the fully charged negative electrode sheet (gray-black area) to the area of the negative electrode sheet is ≤15%; Lithium deposition: Gray-black areas appear locally on the surface of the negative electrode sheet, and the ratio of the lithium deposition area of the fully charged negative electrode to the area of the negative electrode sheet is >15%.
[0174] The test results are shown in Table 1.
[0175] Table 1 Test results
[0176]
[0177]
[0178] From the above data, it can be seen that in Comparative Examples 2, 3 and Examples 2a, 2c, the termination glue 18 covers the positive electrode active material layer, and lithium deposition occurs at the edge of the glue tape after cycling. Comparative Examples 1 and 3 do not dope the ternary material with element M, which will deteriorate the cycle retention rate to a certain extent. In Examples 2a and 5b, the surface density and N / P ratio of the first paste and the second paste are not set within the specified range, and lithium deposition occurs in the outer circle of the negative electrode after cycling. In Example 4a, the positive electrode active material layer is not set with R, and cracks will appear in the aluminum foil at the edge of the paste.
[0179] It should be understood that the term "including" and its variations used in the embodiments of the present application are open inclusions, i.e., "including but not limited to". The term "according to" means "at least in part according to". The term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least another embodiment". The term "plurality" means "more than one", which is intended to cover two, three or more situations.
[0180] It should be understood that although the terms "first" or "second" etc. may be used in the embodiments of the present application to describe various elements, such as a first surface and a second surface, these elements are not defined by these terms, which are only used to distinguish one element from another.
[0181] The protection scope of the embodiments of the present application is not limited to the above embodiments. Any changes or substitutions that can be imagined by any technician familiar with the technical field within the technical scope disclosed in the embodiments of the present application should be included in the protection scope of the embodiments of the present application. Therefore, the protection scope of the embodiments of the present application should be based on the protection scope of the claims.
Claims
1. A wound electrode body, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and a separator which are stacked, wherein the positive electrode sheet and the negative electrode sheet are wound with the separator interposed therebetween, and the wound electrode body has a flat portion and a curved portion; wherein, The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer. Along a first direction Z, the positive electrode current collector has a first surface and a second surface arranged opposite to each other. The first surface is provided with a first paste coating area and a first empty foil area located at the tail of the positive electrode current collector. The second surface is provided with a second paste coating area and a second empty foil area located at the tail of the positive electrode current collector. The positive electrode active material layer comprises a first positive electrode active material layer arranged on the first paste coating area and a second positive electrode active material layer arranged in the second paste coating area. Along a second direction X perpendicular to the first direction Z, at least part of the first empty foil area is provided with a first termination glue. The distance between the side of the first termination glue close to the first positive electrode active material layer and the edge of the first positive electrode active material layer close to the first termination glue is d1, and d1≥0; and The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is Li[Ni x Co y Mn z M 1-x-y-z ]O2 ternary material, M is the metal element doped in the ternary material, 1-xyz>0.
2. The wound electrode body according to claim 1, characterized in that: Along the second direction X, at least part of the second empty foil area is provided with a second termination glue, and the distance between the side of the second termination glue close to the second positive electrode active material layer and the edge of the second positive electrode active material layer close to the second termination glue is d2, and d2≥0.
3. The wound electrode body according to claim 2, characterized in that: The d1 satisfies 0<d1≤A / (B1*2); And / or, d2 satisfies 0<d2≤A / (B2*2); Preferably, A is 30 μm to 100 μm, and B1 and B2 are 15 μm to 30 μm respectively; More preferably, A is 50 μm to 80 μm, and B1 and B2 are 20 μm to 25 μm respectively; wherein, A is the thickness of the paste on one side of the positive electrode sheet, B1 is the thickness of the first termination glue, B2 is the thickness of the second termination glue, and the units of d1 and d2 are mm.
4. The wound electrode body according to claim 2, characterized in that: The end of the first positive electrode active layer near the first paste coating area of the first stop glue is provided with a rounded corner or a chamfered corner; and / or, an end portion of the second positive electrode active layer close to the second paste coating area of the second termination glue is provided with a rounded corner or a chamfer; Preferably, when the rounded corner is provided at the end of the first positive electrode active material layer and / or the end of the second positive electrode active material layer, the radius of the rounded corner is 1 mm to 10 mm; more preferably, the radius of the rounded corner is 2 mm to 6 mm.
5. The wound electrode body according to any one of claims 1 to 4, characterized in that: In the ternary material, 0.5≤x<1, 0≤y≤0.2, 0≤z≤0.3; preferably, 0.8≤x<1, 0≤y≤0.1, 0≤z≤0.1; and / or The M includes at least one of B, Al, Zr, W, Ta, Nb, Ti, Fe, Y, Ga, Cu, Zn, Ge, Mo, V and Cr.
6. The wound electrode body according to any one of claims 1 to 4, characterized in that: The mass percentage of single crystals in the positive electrode active material is 50% to 100%, and the mass percentage of polycrystals is 0% to 50%; Preferably, in the positive electrode active material, the single crystal accounts for 80wt% to 98wt%, and the polycrystalline accounts for 2wt% to 20wt%.
7. The wound electrode body according to any one of claims 1 to 4, characterized in that: The specific surface area of the ternary material is 0.5 m 2 / g~1.5m 2 / g; preferably, the specific surface area of the ternary material is 0.8m 2 / g~1.2m 2 / g; and / or The D of the ternary material 50 2μm~12μm, D max It is 15μm~25μm.
8. The wound electrode body according to any one of claims 1 to 4, characterized in that: The first surface faces the winding center of the wound electrode body, the second surface is away from the winding center, and the compaction density of the positive electrode active material layer is 3.0 g / cm 3 ~3.5g / cm 3 ; and / or The surface density of the positive electrode active material layer is 12 mg / cm 2 ~25mg / cm 2 ; and / or The surface resistance of the positive electrode sheet is 150mΩ to 300mΩ.
9. The wound electrode body according to any one of claims 1 to 4, characterized in that: The first surface faces the winding center of the wound electrode body, the second surface is away from the winding center, and at least in the curved portion, the surface density of the first positive electrode active material layer of the positive electrode sheet is less than the surface density of the second positive electrode active material layer of the positive electrode sheet; Preferably, at least in the bent portion, the surface density of the first positive electrode active material layer is 90% to 99% of the surface density of the second positive electrode active material layer; more preferably, at least in the bent portion, the surface density of the first positive electrode active material layer is 94% to 97% of the surface density of the second positive electrode active material layer; and / or, At least in the bent portion, the thickness of the first positive electrode active material layer is h1, the thickness of the second positive electrode active material layer is h2, and h1<h2; and / or At least in the bent portion, the first positive electrode active material layer is provided with holes or a concave texture structure.
10. The wound electrode body according to claim 9, characterized in that: The surface density of the first positive electrode active material layer is less than the surface density of the second positive electrode active material layer; preferably, the surface density of the first positive electrode active material layer is 90% to 99% of the surface density of the second positive electrode active material layer; more preferably, the surface density of the first positive electrode active material layer is 94% to 97% of the surface density of the second positive electrode active material layer; and / or, The thickness of the first positive electrode active material layer is h1, the thickness of the second positive electrode active material layer is h2, h1<h2; and / or The first positive electrode active material layer is provided with holes or a concave texture structure.
11. The wound electrode body according to any one of claims 1 to 4, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer. Along the first direction Z, the negative electrode current collector has a third surface and a fourth surface arranged opposite to each other, the third surface faces the winding center, and the fourth surface faces away from the winding center. The negative electrode active material layer comprises a first negative electrode active material layer and a second negative electrode active material layer respectively arranged on the third surface and the fourth surface. At least in the bending portion, the N / P ratio of the second negative electrode active material layer to the first positive electrode active material layer is greater than the N / P ratio of the first negative electrode active material layer to the second positive electrode active material layer, and the difference between the two is 0.005 to 0.2; Preferably, the difference between the two is 0.02 to 0.08; wherein, The N / P ratio is the negative electrode capacity per unit area / positive electrode capacity per unit area.
12. The wound electrode body according to claim 11, characterized in that: The N / P ratio of the second negative electrode active material layer to the first positive electrode active material layer is greater than the N / P ratio of the first negative electrode active material layer to the second positive electrode active material layer, and the difference between the two is 0.005 to 0.2; preferably, the difference between the two is 0.02 to 0.
08.
13. A battery, characterized in that: The invention comprises the wound electrode body according to any one of claims 1 to 12.
Citation Information
Cited By
Battery and electric device
CN121546181A